ANALYSIS OF A COMPANY'S BANKRUPTCY PREDICTION USING THE SPRINGATE METHOD AND THE ALTMAN Z-SCORE METHOD - Arumsari, Alifatul Rizka Aji; Marwan, Jubery; Fajarisman, Bambang (Jurnal Indonesia Sosial Sains, 2025)
This study examines the increasing importance of bankruptcy prediction models in the Indonesian banking sector, particularly following recent financial challenges, including the COVID-19 pandemic and evolving regulatory frameworks. This study aims to analyze and predict the potential bankruptcy of a company using two financial analysis methods, namely the Springate method and the Altman Z-Score model. These two methods are used to evaluate the financial health of a company based on significant financial ratios. The Springate method consists of four main ratios that focus on liquidity, profitability, efficiency, and solvency, while the Altman Z-Score uses five ratios covering aspects of liquidity, profitability, leverage, and operational activities to measure bankruptcy risk. The data used in this study are the financial statements of selected companies during a certain period. The results show the accuracy of both methods in predicting corporate bankruptcy, as well as identifying differences in predictions produced by each method. This study provides important insights for company management, investors, and related parties in making decisions based on the identified financial conditions. In addition, it evaluates the strengths and limitations of both methods in the context of bankruptcy analysis across different industries. Thus, this study is expected to contribute to improving financial risk management in companies.